AVAILABILITY AND STORAGE OF HAZARDOUS PRODUCTS IN HOUSEHOLDS IN THE METROPOLITAN REGION OF MANAUS: A POPULATION-BASED SURVEY, 2015 - Gustavo Magno Baldin Tiguman; Marina Borges Dias de Almeida; Marcus Tolentino Silva; Tais Freire Galvao (Sociedade de Pediatria de São Paulo, 2021)
ABSTRACT Objective: The availability of hazardous products in households increases the risks of poisoning. The present study aimed to assess the frequency and associated factors of the availability and storage of hazardous products in residences in the metropolitan region of Manaus. Methods: Population-based and cross-sectional study conducted in 2015 with adults selected with three-stage probabilistic sampling. Participants were interviewed face-to-face. Prevalence ratio (PR) of the presence of hazardous products (presence of chumbinho [illegal anti-cholinesterase rodenticide], artisanal cleaning products, and unsafe storage of these products and medications) and 95% confidence intervals (95%CI) were calculated with Poisson regression with robust variance, weighted by the complex sampling method adopted. Results: A total of 4,001 participants was included, of which 53.0% (95%CI 51.5-54.6) reported presence of hazardous products in their households, 36.3% (95%CI 34.8-37.8) had unsafe storage, 16.2% (95%CI 15.1-17.4) had artisanal cleaning products, and 8.2% (95%CI 7.4-9.1) had chumbinho. Households with children ≤5 years old had safer storage (PR=0.78; 95%CI 0.71-0.86) and more artisanal products (PR=1.30; 95%CI 1.11-1.51). Presence of artisanal products was higher in lower educational levels (PR=2.20; 95%CI 1.36-3.57) and lower economic classifications (PR=1.63; 95%CI 1.25-2.13). Conclusions: Over half of the households in the metropolitan region of Manaus kept hazardous products; one-third stored them unsafely. Artisanal cleaning products and chumbinho were frequently present. Households with children had safer storage of products, and socioeconomic factors affected the availability of such hazardous products.